Sedimentary Record of Polycyclic Aromatic Hydrocarbons in the Gulf of Trieste (Northern Adriatic Sea) - Distribution, Origin and Temporal Trends - Bajt, Oliver (Frontiers in Marine Science, 2022)
A mid-term study (2003-2013) of polycyclic aromatic hydrocarbons in Gulf of Trieste sediments was conducted at seven sampling sites. The PAH spatial and temporal distributions and origin were determined. Sediment samples were collected with a gravity core sampler. Hydrocarbons were extracted from the sediment samples and their concentrations determined by gas chromatography. Principal component analysis (PCA) was performed to determine the differences between the different sampling sites. The results of the study show PAH spatial and temporal variability. The highest mean concentration was measured in the Portoroz marina (1168 ng/g) and the lowest at an offshore site (320 ng/g). The results of the analyses show that the concentrations of PAH are higher in the coastal areas and decrease towards the central part of the Gulf of Trieste. The interannual differences in the concentrations of PAH showed a significant downward trend in the marina of Portorož, in the port of Koper and in the offshore site off Piran. No trend was observed at all other sites. Various evaluation indices showed that PAHs are predominantly of pyrolytic origin, with a smaller proportion of petrogenic substances, especially in the Bay of Koper. PCA analysis confirmed this origin, with Portoroz marina showing a very pronounced pyrolytic origin, and Koper port having a larger proportion of petrogenic origin. Although the investigated area can be considered as only moderately contaminated with PAHs, the applied pollution reduction measures should be continued and intensified.